AB1210-HPR To Explore the Benefits of the Behcet's Information Packs Provided at Diagnosis. (9th June 2015) - Mitton, D.; Situnayake, D.; Carruthers, D.; Murray, P.I.; Damato, E.
Abstract : Background: Good patient information is extremely important within the context of giving the patient confidence. vinvolvement with their care and improves their overall patient experience (NHS 2008). Moreover it provides patients with an aide-memoire of what they have been told. vPatient Information Packs have been designed by the Behcet's Syndrome Society. Objectives: Patient Information Packs have been designed by the Behcet's Syndrome Society. To evaluate the usefulness of these packs it was necessary to undertake an audit to determine the advantages and suggestions of future work needed to improve the content. The Lead nurse wanted to know if the packs were beneficial for patients and did they contain enough/appropriate information at diagnosis. Methods: The packs were designed by the Society and included: Information about the Birmingham Centre, contact details Information about the Behcet Society Society membership form Factsheets about Behcets Syndrome The Behcet's Syndrome Society Support Worker ( BSSW ) distributed Patient Information Packs to patients at their clinical appointment at the Birmingham Behcet's Syndrome Centre of Excellence. A total of 60 patients received the packs over a 6-month period. Two weeks later the Lead Nurse sent out questionnaires to these 60 patients together with a self-addressed stamped envelope. The questionnaires included eight questions asking how the patients felt about the packs. Of these 60 patients, 34 questionnaires were returned (response rate 34.3%), of these 34 patients 32 (94%) had a confirmed diagnosis of Behcet's Syndrome. Results: Questions asked: Have you been diagnosed with Behcets Syndrome? What is your age group? Did you receive a pack at your appointment? Did you find it useful? If not why not? Was there enough information for you? Would you recommend a pack to another patient? Would you make any changes to the pack? 32/34 (94%) of the patients found it useful and that it contained an appropriate amount of information. 0/34 (%) patients would recommend the pack to another patient. Only one patient suggested making an alteration to the pack. Conclusions: It is essential for the National Centres of Excellence to maintain and continue to improve information for patients and carers regarding Behcets Syndrome including future research projects. The audit has shown that the majority of patients have found the packs to be beneficial and provides the right amount of appropriate information. However as possible new treatments and management of the symptoms of Behcets Syndrome increase the packs may require regular up dates. The Lead nurse has noticed that perhaps current research being undertaken into Behcets Syndrome should also be included, this would provide patients with an up to date knowledge and education about research and possibly aid the option to participate into current research projects. References: NHS (2008) Patient information: Institute for innovation and improvement. Disclosure of Interest: None declared